2020
DOI: 10.1002/mren.202000029
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Biohybrid Particles by Modification of Chitosan Beads via RAFT Polymerization in Dispersed Media

Abstract: in various fields including, water and wastewater treatment as adsorbents or coagulation-flocculation agents, medical applications as drug delivery systems, and the cosmetic or agriculture sectors. [2,4,8] However, the properties of unmodified CTS limit its use for some applications. Consequently, researchers have focused on the modification of CTS to improve and tune its properties, such as improved solubility in organic solvents, compatibility with various polymers, or affinity for molecules of interest. Pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 88 publications
(109 reference statements)
0
6
0
Order By: Relevance
“…XCTS-CPS-g-P4VP maintained its ability after being cycled 7 times with 61%-62% of the initial adsorption retained after the seventh cycle. [42] Modified chitosan with phosphorous groups also may be a promising candidate for applications in wastewater treatment, anticorrosion of coatings, or as flame retardancy material. [41] Our research group has also investigated applications for the modified CNC.…”
Section: Applications Of Polymer Modified Polysaccharidesmentioning
confidence: 99%
See 2 more Smart Citations
“…XCTS-CPS-g-P4VP maintained its ability after being cycled 7 times with 61%-62% of the initial adsorption retained after the seventh cycle. [42] Modified chitosan with phosphorous groups also may be a promising candidate for applications in wastewater treatment, anticorrosion of coatings, or as flame retardancy material. [41] Our research group has also investigated applications for the modified CNC.…”
Section: Applications Of Polymer Modified Polysaccharidesmentioning
confidence: 99%
“…CNC is currently a material of significant interest to the scientific community due to the all the properties that a single material can present. [8,29,43,44] The primary S C H E M E 1 0 Synthesis scheme to obtain functionalized chitosan (CTS-CPA), grafting from polymerization reactions of 4VP (CTS-CPAg-P4VP), and crosslinking of the beads (XCTS-CPA-g-P4VP) [42] objective of our research was to modify the surface properties of CNC to make it compatible with more hydrophobic systems and/or stimuli-responsive. We explored the modification of CNC (made by acid hydrolysis) with grafted polymers via RDRP both via grafting from and grafting to approaches.…”
Section: Polymer Grafting Modification Of Cnc Via Reversible Deactivation Radical Polymerizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, after yielding the macroparticles modified with P4VP, these were cross-linked with dialdehyde (producing XCTS-CPS-g-P4VP) in order to improve chemical and mechanical resistance for further applications. [42]…”
Section: Polymer Graft Modification Of Chitosan Via Nitroxide-mediate...mentioning
confidence: 99%
“…In this case, the adsorption of bisphenol (BPA) from water was studied. [42] BPA presents significant hazards to human health and it has been used in the plastic industry and had been found in water for food for human consumption; therefore, its removal from water can be of significant importance. By adsorption kinetics studies, it was observed that modified XCTS-CPS-g-P4VP performed considerably better than native chitosan, especially the chitosan modified with larger P4VP chains.…”
Section: Applications Of Polymer Modified Polysaccharidesmentioning
confidence: 99%